Female Olympian and Paralympian Events Analyses, Backgrounds, and Timelines - Fuller, Linda K. (Springer International Publishing, 2018)
Female Olympian and Paralympian Events is a groundbreaking book that examines women's sports in the Olympic and Paralympic Games, which have long been underappreciated and under-analyzed. The book begins with a brief background on women's participation in the Olympic Games and their role relative to the International Olympic Committee, then introduces the underlying Gendered Critical Discourse Analysis theory used throughout the book's analysis before delving into a literature review of female Olympians and Paralympians' events. It includes a listing of noteworthy "firsts" in the field, followed by individual discussions of twenty-eight Summer and seven Winter events, analyzed according to their historical, rhetorical, and popular cultural representations. Women's unique role(s) in the various events are discussed, particular athletes and Paralympic events are highlighted, and original tables are also included. At the end of each section, affiliated organizations and resources are included in this invaluable referential volume.